Polymorphism in 1908STR1934 locus of the 3' UTR of the Nramp1 bovine gene in eight cattle breeds - González S., Jenny P.; Saldarriaga, Omar A.; López Herrera, Albeiro; Bermúdez, Nelson R.; Zapata Builes, Wildeman; Ossa Londoño, Jorge; Rugeles Lopez, María Teresa; Bedoya B., Gabriel (Revista Colombiana de Ciencias Pecuarias, 2016)
Summary The Nramp1 gene has been associated with natural resistance to intracellular microorganisms in several species including bovine. Recent evidence suggests an association between polymorphism in the 3´ untranslated region (3´ UTR) of this gene with resistance/susceptibility (R/S) to Brucella abortus as determined in vivo and in vitro. In this study we tested for the variability of the short tandem repeat (STR) within the 3´ UTR of Nramp1 in six breeds of Colombian creole cattle (CCC) and compared the genotypes with those of Holstein and Brahman, which were recently introduced into this country. In CCC as well as in Holstein we found the allele 175 fixed in all populations. In Brahman, 175 allele was also present with a frequency of 0.467 but additionally, in this breed there appeared five other alleles and among them two previously unreported: 183 y 185; also was found the allele 189 in the Colombian creole Harton del Valle cattle, which is not previously reported. Together these results suggest that the 175 allele in the 3´ UTR Nramp1 may be an ancestral allele in cattle and if this is true the association previously reported with the R/S trait requires further evaluation. Key words: colombian creole cattle, microsatellite, Nramp1, 3´ UTR. Resumen Análisis de polimorfismos en el locus 1908STR1934 locus del 3´ UTR del gen Nramp1 bovino en ocho razas de ganado El gen Nramp1 ha sido asociado con resistencia natural a microorganismos intracelulares en varias especies incluyendo bovinos. Evidencia reciente sugiere una asociación in vivo e in vitro, entre el polimorfismo en la región 3´ no traducida (3´ UTR del inglés 3´ untranslated region) de este gen con resistencia susceptibilidad (R/S) a Brucella abortus. En este estudio se evaluó la variabilidad de una secuencia repetida en tandem (STR, del inglés short tandem repeat) dentro del 3´ UTR de Nramp1 en seis razas de ganado criollo colombiano (GCC) y se comparó con la variabilidad de los de ese STR en Holstein y Brahman, razas que fueron recientemente introducidas a este país. En GCC así como en Holstein se encontró que el alelo 175 está fijado en todas las poblaciones. En Brahman. El alelo 175estuvo presente con una frecuencia de 0.467, pero adicionalmente en este ganado aparecieron otros 5 alelos, dos de ellos no habían sido previamente reportados: 183 y 185; también se encontró el alelo 189 en el ganado criollo colombiano Hartón del Valle, el cual no está reportado previamente. Estos resultados sugieren que el alelo 175 en el 3´ UTR de Nramp1 puede ser un alelo ancestral en ganado y si esto es cierto, la asociación previamente reportada con la característica de R/S requiere evaluación futura.